A modified immuno-enriched 32P-postlabeling method for analyzing the malondialdehyde−deoxyguanosine adduct, 3-(2-Deoxy-β-d-erythro-pentofuranosyl)- pyrimido[1,2-α]purin-10(3H)one in human tissue samples - Sun, Xin; Nair, Jagadeesan; Bartsch, Helmut (Chemical research in toxicology, 2004)
The malondialdehyde-modified DNA adduct, 3-(2-deoxy-β-d-erythro-pentofuranosyl)pyrimido[1,2-α]purin-10(3H)one (M1dG) has been detected in human tissues and is considered to be a promising biomarker for estimating lipid peroxidation-induced DNA damage. With the aim to analyze the M1dG in small amounts of DNA (<10 μg) and to improve the sensitivity, we have developed an immuno-enriched 32P-postlabeling HPLC method. The main modifications included the following steps:  (i) an optimization of the immunoenrichment conditions using a monoclonal antibody (MAb D 10A1), (ii) a single labeling step of the purified M1dG 3‘-monophosphate to its 5‘-monophosphate at pH 6.8, (iii) the addition of O4-ethylthymidine 3‘-monophosphate as an internal standard, and (iv) a prepurification of the labeled adduct on a polyethyleneimine minicolumn before HPLC analysis. With this protocol, the percent recovery of M1dG was found to be ∼70 ± 20; the detection limit in biological samples was ∼200 amol M1dG from 10 μg of DNA, corresponding to 6 adducts/109 nucleotides. In conclusion, our modified method shows a high sensitivity and specificity; when applied to human breast and liver tissue samples, background levels of the M1dG could be reproducibly detected. This ultrasensitive detection method is thus suitable for applications in human biomonitoring and molecular epidemiology studies.
Im Titel ist "32" bei "P" hochgestellt
Gesehen am 11.12.2020